PERBANDINGAN KINERJA KEUANGAN PEMERINTAH KOTA LANGSA DENGAN PEMERINTAH KABUPATEN ACEH TIMUR - Tuti Meutia (Jurnal Samudra Ekonomika, 2021)
The purpose of this study was to analyze the comparison of the financial performance of the Langsa City government and East Aceh Regency. Financial performance is measured using five indicators, namely efficiency ratios, effectiveness ratios, compatibility ratios, growth ratios and radiant ratios. The results of the study stated that the financial efficiency ratio of Langsa City during the observation period was more efficient than that of East Aceh Regency. The financial effectiveness ratio of East Aceh Regency during the observation period was more effective than that of Langsa City. The Conformity Ratio measured by the value of the ratio of operating expenditures shows that Langsa City is high when compared to East Aceh District, the APBD and PAD growth ratios of the two regions are both in positive values. The operating expenditure growth ratio of Langsa City is better because it shows a lower ratio value compared to East Aceh District and the operating expenditure growth ratio of East Aceh Regency during the observation period is on average higher. This is evidenced by the value of the ratio of operating expenditures in East Aceh Regency on average each year above 10%. East Aceh District is more capable of self-financing government activities than Langsa City. The pattern of self-reliance is in the consultative and participatory categories. The value of the regional financial independence ratio of Langsa City is in the Instructive relationship pattern (Langsa City is not able to implement regional autonomy financially).